2003
DOI: 10.1074/jbc.m211598200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Mixed Lineage Kinase 3 by Protein Kinase B/AKT Leads to Cell Survival

Abstract: Mixed lineage kinase 3 (MLK3) is a mitogen-activated protein kinase kinase kinase (MAPKKK) that activates c-jun N-terminal kinase (JNK) and can induce cell death in neurons. By contrast, the activation of phosphatidylinositol 3-kinase and AKT/protein kinase B (PKB) acts to suppress neuronal apoptosis. Here, we report a functional interaction between MLK3 and AKT1/PKB␣. Endogenous MLK3 and AKT1 interact in HepG2 cells, and this interaction is regulated by insulin. The interaction domain maps to the C-terminal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 22 publications
9
127
0
Order By: Relevance
“…Previous reports have shown that the inactivation of the PI3K/ Akt pathway allows for the activation of MLK and/or JNK, which leads to apoptosis. 31,36,37 In the current study, inhibitors of MLK, p38 or JNK did not prevent the peroxynitrite-induced dephosphorylation of Akt but still prevented apoptosis (Figures 1 and 7). Akt dephosphorylation was not detected until 16 h after exposure to peroxynitrite (not shown) suggesting that inactivation of PI3-K/Akt and activation of MLK/p38/ JNK are autonomous pathways that converge, perhaps at the level of Bax translocation ( Figure 9).…”
Section: Discussionmentioning
confidence: 44%
“…Previous reports have shown that the inactivation of the PI3K/ Akt pathway allows for the activation of MLK and/or JNK, which leads to apoptosis. 31,36,37 In the current study, inhibitors of MLK, p38 or JNK did not prevent the peroxynitrite-induced dephosphorylation of Akt but still prevented apoptosis (Figures 1 and 7). Akt dephosphorylation was not detected until 16 h after exposure to peroxynitrite (not shown) suggesting that inactivation of PI3-K/Akt and activation of MLK/p38/ JNK are autonomous pathways that converge, perhaps at the level of Bax translocation ( Figure 9).…”
Section: Discussionmentioning
confidence: 44%
“…In Vitro Kinase Assay-The in vitro kinase assays were performed according to the protocol described elsewhere (55). Equal amounts of total protein lysate, extracted from cells treated as indicated, were immunoprecipitated by an antibody against GSK3␤ pre-adsorbed to protein ASepharose beads.…”
Section: Methodsmentioning
confidence: 99%
“…Equal amounts of total protein extracted from AGSE cells was subjected to Western blot and immunoprecipitation analysis, as described (Rana et al, 1995;Barthwal et al, 2003). Proteins were detected using appropriate primary and secondary antibodies and developed using the Enhanced Chemiluminescence system (Pierce, IL, USA).…”
Section: Western Blot and Immunoprecipitation Analysismentioning
confidence: 99%